Synthetic Utility of the Vilsmeier–Haack Reagent in Organic Synthesis - Neena, Neena; Chaudhri, Vishwas; Singh, Fateh V.; China, Hideyasu; Dohi, Toshifumi; Kumar, Ravi (Synlett, 2023)
The Vilsmeier–Haack reaction has historically been a topic of significant interest to organic chemists, and it continues to attract considerable attention. The reaction itself provides a facile route towards a large number of aromatic and heteroaromatic systems. The Vilsmeier–Haack reagent, generated from amides and halides, is found to be very important in organic synthesis. This account highlights recent developments in the synthetic utility of the Vilsmeier–Haack reagent.1 Introduction2 Formylation3 Formylation and Chlorination4 Formylation and Acetylation5 Chlorination6 ortho-Formylation7 Miscellaneous8 Conclusions
Keywords: Vilsmeier–Haack reagent; formylation; chlorination; heterocycles